2019
DOI: 10.1002/jcla.23146
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in MALAT1 with the risk of endometrial cancer in Southern Chinese women

Abstract: Background: Endometrial cancer is the most common gynecologic malignancy worldwide. Polymorphisms in MALAT1 have been demonstrated to play critical roles in cancer. However, the roles of MALAT1 polymorphisms in the etiology of endometrial cancer have not been well documented. Methods:We genotyped three MALAT1 polymorphisms in 249 endometrial cancer cases and 446 cancer-free female controls using quantitative polymerase chain reaction with TaqMan probes. To estimate the association between MALAT1 polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Chen et al (73) demonstrated the association of MALAT1 rs664589 C>G polymorphism with the risk of endometrial cancer in Southern Chinese women. It was demonstrated that individuals with CGG haplotypes have a higher risk of developing endometrial cancer compared with the wild-type GCG haplotype carriers (73). Collectively, these findings suggest the potential role of MALAT1 in inducing the development of different gynecological cancers.…”
Section: Pathogenic Role Of Malat1 In Gynecological Cancersmentioning
confidence: 86%
“…Chen et al (73) demonstrated the association of MALAT1 rs664589 C>G polymorphism with the risk of endometrial cancer in Southern Chinese women. It was demonstrated that individuals with CGG haplotypes have a higher risk of developing endometrial cancer compared with the wild-type GCG haplotype carriers (73). Collectively, these findings suggest the potential role of MALAT1 in inducing the development of different gynecological cancers.…”
Section: Pathogenic Role Of Malat1 In Gynecological Cancersmentioning
confidence: 86%
“…In addition to NSCLC, MALAT1 is also present in other malignant tumors. In endometrial cancer, the expression of MALAT1 is negatively correlated with the expression of miR-200c, and its knockdown can promote the expression of miR-200c in cancer cells [28]. Studies have found that MALAT1 can also adjust the expression of miR-140 in prostate cancer cells to change the mRNA and protein expression levels of apoptosis inhibitor protein to promote the occurrence and development of tumors [29].…”
Section: Discussionmentioning
confidence: 99%
“… 40 Single nucleotide polymorphisms (SNPs) in Malat1 DNA, such as Rs664589C>G, have been shown to significantly increase the risk of endometrial cancer when tested in tissue samples and peripheral blood and following the application of logistic regression analyses. 41 In addition, the expression levels of Malat1 have been found to be related to tumor type, metastatic lymph nodes, and recurrence rate. 42 …”
Section: The Clinical Relevance Of Malat1 In Gynecological Malignancimentioning
confidence: 99%